Pengembangan model latihan konsentrasi pada tembakan free throw pemain bola basket - Iskandar, Dedi; Ramadan, Gilang (Universitas Nusantara PGRI Kediri, 2019)
The purposes of this study were to develop a concentration training model on free throw shots basketball players and to measure the extent of the process of concentration training model on free throw shots basketball players. The process of this research began with a need analysis with field observation method and continued with the process of the development of a concentration training model on free throw shots basketball players according to the characteristics needed. The development of this training model was carried out by applying 10 steps according to Brog and Gall and producing a product from concentration training model on free throw shots basketball players according to the needs and the suitability needed. Based on the results of the analysis on the small group trials the average choice was 82.10%, whereas in the medium group trials the average values obtained was 87.56%, while in the large group trials the average choice was 90.49 %. This stated that the concentration training model on free throw shots basketball players was very feasible to use.